Do bond investors attend to corporate targeted poverty alleviation? - Hongxian Zhen; Sanfa Wang; Mingxiang Lian; Shijie Zheng (China Journal of Accounting Studies (CJAS), 2022)
This paper incorporates corporate targeted poverty alleviation behaviour into the bond pricing framework for the first time, using a sample of A-share listed companies that issued corporate bonds from 2016 to 2018 to study the impact and mechanism of targeted poverty alleviation behaviour on bond credit spreads. We find that bond-issuing companies' targeted poverty alleviation behaviour can significantly reduce bond credit spreads, which are more pronounced in subsamples with higher credit risk and lower credit rating and of active participants. In addition, companies' targeted poverty alleviation behaviour has improved corporate reputation and strategic resource acquisition and reduced information asymmetry and agency costs. Consequently, these results indicate that corporate targeted poverty alleviation is essentially embodied as value features, not tool features, and bond investors can identify the true motivations of engaged enterprises.
Keywords: 650; Targeted poverty alleviation; bond credit spreads; motivation for targeted poverty alleviation